CFD study on the effect of ultrasound wave frequency on cavitation field inside a liquid - Masoud Rahimi1; Mahdieh Abolhasani; Maryam Dehbani; Ammar.A. Alsairafi (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia